Efficiency of commercial banks in Turkey and their comparison: Application of DEA with Tobit analysis - Kutlar A.; Kabasakal A.; Ekici M.S. (Inderscience Enterprises Ltd., 2017)
This paper aims to investigate the technical and allocative efficiency scores of 23 commercial banks operating in Turkey between 2003 and 2012 by using data envelopment analysis (DEA). In the CCR model analysis, the number of technically inefficient banks rises from three to six and the number of allocatively inefficient banks falls from six to five within the given period. On the other hand the number of technically efficient banks falls from 22 to 19 whereas the number of allocatively efficient banks rises from 10 to 16 in the study period according to BCC model analysis. Subsequently, the efficiency scores of the companies are associated with the outputs in the Tobit regression, and we try to determine the decisiveness of the outputs on efficiency. According to our results Tobit analysis provides more appropriate results on allocative efficiency scores in comparison to technical efficiency scores with the same output compound. © 2017 Inderscience Enterprises Ltd.
Keywords: Banking; Data censoring; Data envelopment analysis; Data truncating; DEA; Operational research; Tobit analysis; Turkey